Evaluation of rural competitiveness: Case study Romania - Monica Mihaela Tudor (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
Regional competitiveness, understood as the ability of regions to promote, attract and sustain the economic activity, so that their population can reach and maintain a high living standard, is the object of the present analytical approach. The results of the study reveled that the economy of the predominantly rural regions is less competitive than the economy of the intermediate regions. The factors that mainly contribute to widening the territorial disparities in rural competitiveness are the following: i) size of RDI staff that provides the comparative advantage of the access to innovation and ii) value of exports, both in the non-agricultural and in the agri-food economy, certifying the competitive advantage of regional economies on the international markets.
Keywords: O11; O18; R58; 330; regional competitiveness; rural area; Romania